Patient satisfaction with tele-advice during the COVID-19 pandemic - Gieniec, Weronika; Jurkiewicz, Beata (Health Promotion & Physical Activity, 2021)
Introduction: The coronavirus pandemic has shed a whole new light on telehealth, which has become an alternative for diagnosis, monitoring, treatment and support without physical contact between patient and healthcare professional. The aim of this study was to examine patient satisfaction with medical services provided with tele-advice during the Covid-19 pandemic. Material and methods: The study was conducted using our own questionnaire via Google Form that was correctly completed by 133 individuals between the ages of 18 and 76 years (mean 33.1 ± 13.1 years) who received medical services via tele-advice. Results: Patients with chronic conditions were statistically more likely to seek specialist services via tele-advice (p = 0.003). Slightly less than one-third of respondents (n = 39; 29.3%) were asked during the tele-advice to attend the clinic / office in person to complete the visit with a physical examination. The vast majority of subjects (n = 95; 71.4%) responded that their health status had not changed since the pandemic and the introduction of tele-advice. Nearly half (n = 64; 48.1%) believed that their health problem had been solved via tele-advice. Only 4.5% of the respondents (n = 6) strongly agreed with the statement that “tele-advice enables proper diagnosis and matching of effective treatment”, 18.0% (n = 24) tended to agree. The vast majority of respondents believed that everyone should be able to choose between tele-advice and a traditional medical visit (n = 121; 91.0%). Conclusions: The majority of people surveyed did not perceive a difference in their health since the pandemic and the introduction of tele-advice. Nearly half of respondents believed that their health problem had been resolved with a telemedicine consultation, with even fewer people convinced that “tele-advice allows for proper diagnosis and matching of effective treatment.” Patients would mostly like to have a choice between tele-visit and in-person visits, with no clear indication of the superiority of one or the other. Continuous improvement of current solutions will certainly contribute to increased patient satisfaction with the medical services provided.